If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1 + -1i)(1 + 2i)(1 + -3i) = 0 Multiply (1 + -1i) * (1 + 2i) (1(1 + 2i) + -1i * (1 + 2i))(1 + -3i) = 0 ((1 * 1 + 2i * 1) + -1i * (1 + 2i))(1 + -3i) = 0 ((1 + 2i) + -1i * (1 + 2i))(1 + -3i) = 0 (1 + 2i + (1 * -1i + 2i * -1i))(1 + -3i) = 0 (1 + 2i + (-1i + -2i2))(1 + -3i) = 0 Combine like terms: 2i + -1i = 1i (1 + 1i + -2i2)(1 + -3i) = 0 Multiply (1 + 1i + -2i2) * (1 + -3i) (1(1 + -3i) + 1i * (1 + -3i) + -2i2 * (1 + -3i)) = 0 ((1 * 1 + -3i * 1) + 1i * (1 + -3i) + -2i2 * (1 + -3i)) = 0 ((1 + -3i) + 1i * (1 + -3i) + -2i2 * (1 + -3i)) = 0 (1 + -3i + (1 * 1i + -3i * 1i) + -2i2 * (1 + -3i)) = 0 (1 + -3i + (1i + -3i2) + -2i2 * (1 + -3i)) = 0 (1 + -3i + 1i + -3i2 + (1 * -2i2 + -3i * -2i2)) = 0 (1 + -3i + 1i + -3i2 + (-2i2 + 6i3)) = 0 Combine like terms: -3i + 1i = -2i (1 + -2i + -3i2 + -2i2 + 6i3) = 0 Combine like terms: -3i2 + -2i2 = -5i2 (1 + -2i + -5i2 + 6i3) = 0 Solving 1 + -2i + -5i2 + 6i3 = 0 Solving for variable 'i'. The solution to this equation could not be determined.
| (1-j)(1+2j)(1-3j)=0 | | 4h-3(2-h)=2(h+7) | | 200=8x+x^2 | | 1.6=log(x/5) | | -5-2y=5 | | 4x-3(6+2x)=-14 | | v=u | | cos^2x-cos-2=0 | | 60=2h-7+7 | | 2x^2-4x+p=0findvaluesp | | x^3-12x^2+60x-48=0 | | -10.5z-63=2z-15 | | 2n+7=5n-8 | | (x*10)/100=110-x | | 2(4a+5)+134=80(a+9) | | 4a2-a/a | | y=99.828x | | log(x)=1.79 | | 2.0317x^2+65.56x=0 | | y=2.0317x^2+65.56x | | 5x-19=2x+12 | | 21/57 | | f(x)=x(2x-1)(x+4) | | 2sin(x)=2-3cos^2(x) | | 40-19=3(x-4) | | 8-72y=95-15y | | 7x^2+2x-15=0 | | Y(1-x)DX+x(1+y)dy=0 | | 2t+4u=40 | | 27-17=5(x-8) | | 20x-16=18x+6 | | -(13+g)=-9 |